2010
DOI: 10.15288/jsad.2010.71.819
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of Older Foster Youths With Differential Risk of Diagnosis for Alcohol Abuse or Dependence

Abstract: ABSTRACT. Objective: Distinctive combinations of factors are likely to be associated with serious alcohol problems among adolescents about to emancipate from the foster care system and face the diffi cult transition to independent adulthood. This study identifi es particular subpopulations of older foster youths that differ markedly in the probability of a lifetime diagnosis for alcohol abuse or dependence. Method: Classifi cation and regression tree (CART) analysis was applied to a large, representative sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…Using the same data, Keller, Blakeslee, Lemon, & Courtney (2010) used classification and regression tree analysis to examine different probabilities of receiving a diagnosis of lifetime Alcohol Abuse or Alcohol Dependence. Results indicated that, when including both behavioral indicators (e.g., delinquency, school problems) and environmental circumstances (e.g., placement history, support from caregivers), several profiles of youth existed.…”
Section: Youth Currently In Foster Carementioning
confidence: 99%
“…Using the same data, Keller, Blakeslee, Lemon, & Courtney (2010) used classification and regression tree analysis to examine different probabilities of receiving a diagnosis of lifetime Alcohol Abuse or Alcohol Dependence. Results indicated that, when including both behavioral indicators (e.g., delinquency, school problems) and environmental circumstances (e.g., placement history, support from caregivers), several profiles of youth existed.…”
Section: Youth Currently In Foster Carementioning
confidence: 99%
“…Yine Amerika'da (2020) genç yetişkinlerde madde kullanım bozuklukları açısından birçok gelişimsel risk faktörünün değerlendirildiği bir araştırmada; olumsuz çocukluk deneyimlerine ek olarak 18 yaşından önce evsizlik deneyiminin olmasının alkol kullanım bozukluğu, tütün kullanım bozukluğu ve kannabis kullanım bozukluğu ile anlamlı bir şekilde ilişkili olduğu, koruyucu aile bakımının (foster care) ise kendisinin birden fazla olumsuz çocukluk deneyimleri karşısında madde kullanım bozuklukları açısından bir risk faktörü olmadığı, koruyucu aile sisteminin bir miktar koruma sağlayabileceği bildirilmiştir (21). Buna karşın bu konuda aksi sonuçlar gösteren başka araştırmalar da mevcut olup, koruyucu aile bakım hizmeti içerisinde yer alan gençlerdeki en yaygın ruh sağlığı sorunlarının madde kullanım bozuklukları olduğu, alkol ve madde kullanım yaygınlık oranlarının bu gençlerde koruyucu aile bakım hizmetine dâhil olmayanlara göre 2 ila 5 kat daha yüksek olduğu bildirilmiştir (24).…”
Section: Madde Kullanım Riski Ve Koruyucu Faktörlerunclassified
“…They often experience few protective factors and a high degree of risk factors for problem substance use, including family substance use history, parent psychopathology, poor family relationships and family management, unstable living situations, poor educational attainment, history of abuse/neglect, conduct disorder and delinquent behavior, and a stressful life (Courtney et al, 2004, 2005; Davis, 2006; Hawkins, Catalano, & Miller, 1992; McMillen et al, 2005; Pecora et al, 2003; Salazar, Keller, Gowen, & Courtney, 2013; Scherr, 2007; Stone, Becker, Huber, & Catalano, 2012; Traube, James, Zhang, & Landsverk, 2012). Several studies have found leaving state care or living in an independent living setting to be a risk factor for increased substance misuse for transition-aged foster youth (Keller, Blakeslee, Lemon, & Courtney, 2010; Narendorf & McMillen, 2010; Thompson & Auslander, 2007; Vaughn et al, 2007). Due to the higher vulnerability of young people with foster care experience developing a substance use disorder, along with a lack of financial and relationship supports when aging out of care (Courtney & Dworsky, 2006; Day et al, 2012; Perry, 2006; Salazar, Keller, & Courtney, 2011), the availability of effective programming that addresses substance abuse prevention and early intervention along with postsecondary achievement is especially important for life success.…”
Section: Introductionmentioning
confidence: 99%